Exploring The Interest of Female Students Towards Physics - Ghimire, Rajan (The Journal of Aadikavi, 2024)
This research study aims to identify effective strategies for promoting greater interest and engagement in physics among female students at the secondary level. Despite the pivotal role of physics in understanding the natural world, there exists a persistent gender gap in the field, with women being underrepresented in physics-related careers and academic programs. The study focuses on understanding the perceptions and attitudes of female students towards physics, as these factors significantly influence their academic choices and career aspirations. By addressing the gender gap in STEM fields, the research seeks to foster inclusivity and encourage greater female participation in the scientific community. Using a qualitative approach, the study explores school-level factors that impact girls' involvement and achievements in physics, including pedagogy, school organization, and environment. Through focus group discussions and in-depth interviews, insights are gathered from female students in secondary schools in Tanahun district, Nepal.The research aims to provide a comprehensive understanding of the challenges faced by female students in physics education and to identify strategies that can effectively address these challenges. By bridging gaps in existing knowledge, the study contributes to enhancing gender equality in physics education and lays the groundwork for targeted interventions and initiatives to promote greater interest and engagement among female students in the subject.